Glycosphingolipid Domains on Cell Plasma Membrane. Issue 3 (June 1999) - Sorice, Maurizio; Garofalo, Tina; Misasi, Roberta; Dolo, Vincenza; Lucania, Giuseppe; Sansolini, Tiziana; Parolini, Isabella; Sargiacomo, Massimo; Torrisi, Maria Rosaria; Pavan, Antonio
Abstract : In this study we analyzed by immunofluorescence, laser confocal microscopy, immunoelectron microscopy and label fracture technique the ganglioside distribution on the plasma membrane of several different cell types: human peripheral blood lymphocytes (PBL), Molt-4 lymphoid cells, and NIH 3T3 fibroblasts, which mainly express monosialoganglioside GM3, and murine NS20Y neuroblastoma cells, which have been shown to express a high amount of monosialoganglioside GM2. Our observations showed an uneven distribution of both GM3 and GM2 on the plasma membrane of all cells, confirming the existence of ganglioside-enriched microdomains on the cell surface. Interestingly, in lymphoid cells the clustered immunolabeling appeared localized over both the microvillous and the nonvillous portions of the membrane. Similarly, in cells growing in monolayer, the clusters were distributed on both central and peripheral regions of the cell surface. Therefore, glycosphingolipid clusters do not appear confined to specific areas of the plasma membrane, implying general functions of these domains, which, as structural components of a cell membrane multimolecular signaling complex, may be involved in cell activation and adhesion, signal transduction and, when associated to caveolae, in endocytosis of specific molecules.